Learning across teams in project-oriented organisations: the role of programme management. Issue 1 (29th August 2021) - de Groot, Bert; Leendertse, Wim; Arts, Jos
Abstract : Purpose: Learning across teams and organisational levels enables organisations to deal with challenges that arise from changing contexts. Project-oriented organisations increasingly use programme management to cope with such challenges and improve performance. This paper aims to find out how different programme configurations affect learning across project teams and between project teams and their parent organisation in project-oriented organisations. Design/methodology/approach: A case study of a project-oriented organisation involved in five infrastructure programmes was performed. Findings: The studied programmes linked learning processes at group and organisational levels by creating relationships across project teams and their parent organisation and acting as a knowledge centre. Team learning benefits from the learning culture and stable environment that programmes create for project teams. This study indicates that a programme's features and focus strongly determines whether a programme predominantly enhances learning across project teams or learning between project teams and their parent organisation. Originality/value: Although programme management is increasingly used by project-oriented organisations, there are few studies relating to learning in programmes. This study provides new insights into learning across teams through programmes.